Tetanus - Poudel, P; Budhathoki, S; Manandhar, S (Kathmandu University Medical Journal, 2010)
Tetanus is now a rare disease in developed world. However it remains an important cause of death worldwide and is associated with a high case fatality, particularly in the developing world. Tetanus is caused by contamination of wound by spores of Clostridium tetani. Neonatal tetanus results from contamination of the umbilical stump at or following delivery of a child born to a mother who did not possess sufficient circulatory antitoxin to protect the infant passively by transplacental transfer. It produces its clinical effects via a powerful exotoxin, tetanospasmin, which leads to uncontrolled disinhibited efferent discharges from motor neurons in the spinal cord and brainstem, causing intense muscular rigidity and spasm. Shorter incubation and onset times are associated with more severe disease and poorer prognosis. Four clinical forms of tetanus are recognised. They are generalised, localised, cephalic and neonatal tetanus. Tetanus is associated with several complications like respiratory failure, cardiovascular instability, renal failure and autonomic dysfunctions. Recovery from tetanus takes a long time. Diagnosis is established clinically. Symptomatic management, early recognition of complications, careful monitoring for dysautonomia and respiratory assistance are the anchors for successful outcome of patients. Tetanus is preventable through vaccination. Vaccination is highly safe and efficacious. Active immunisation should be instituted in all partially immunised, unimmunised persons and those recovering from tetanus. Passive immunisation is given as treatment of a case as well as prevention following high risk injury. Nepal has achieved neonatal tetanus elimination status on 2005 and is running different programs to sustain the status. Key words: Tetanus; neonatal tetanus; spasm; treatment; immunisation. DOI: 10.3126/kumj.v7i3.2744 Kathmandu University Medical Journal (2009) Vol.7, No.3 Issue 27, 315-322